Gamification Learning Model to Improve Conceptual Understanding of Aqidah Akhlak Subject - Nisaul Barokati Seliro Wangi; Muh Barid Nizarudin Wajdi (Al-Hayat: Journal of Islamic Education, 2022)
This research investigates the effectiveness of gamification methods in improving learning outcomes, focusing on conceptual understanding and instilling faith and moral values among Madrasah Ibtidaiyah (MI) students. This research uses a quantitative approach to a quasi-experimental design with a non-equivalent control group. Involving 360 MI students as a population with a sample size of 135 students from three locations as research subjects. Data collection techniques include administering tests and questionnaires. Data analysis was done using t-test statistical techniques and multiple linear regression analysis. Research findings showed significant improvements in both areas among students who participated in the gamification learning model. The analysis results show that the gamification learning model contributes 32.7% to students' understanding of religious and moral concepts, with a regression coefficient of 0.57 and a determination coefficient of 0.327, indicating a strong positive relationship between the gamification learning model and increasing conceptual understanding. Student. In addition, the results of statistical tests show that the gamification learning model positively affects the motivation, engagement and academic achievement of MI students in religious and moral subjects. Implementing this model successfully attracts attention, increases the material's relevance, builds self-confidence, and provides satisfaction to students in the learning process. Integrating the MDA Framework with game elements such as points, levels, rewards and challenges has also increased the effectiveness of religious and moral learning. These findings underscore the importance of integrating gamification into MI education to improve learning outcomes and value education, offering valuable insights for educational practitioners and researchers aiming to innovate pedagogical strategies within the MI education framework.